Ответы и объяснения

  • fuflunce
  • почетный грамотей
2012-12-05T13:39:04+00:00

45*3^(2x)-98*3^x*5^x-75*5^(2x)=0   /Разделим уравнение на 5^x
 45*(3/5)^(2x)-98*(3/5)^x-75=0
Пусть (3/5)^x = t, тогда
45t^2 - 98t - 75 = 0
D = b^2 - 4ac = 98^2 + 4*45*75 = 23104 = 152^2
t = [-b +- (D)^0.5]/2a = (98 +- 152)/90
t1 = 25/9       t2 = -3/5
 (3/5)^x = t

1)  (3/5)^x = 25/9

     (3/5)^x = (3/5)^(-2)
             x = -2
2)  (3/5)^x = -3/5
     решений нет, т.к. показательна функция - положительная

Следовательно, ответ: х = -2